The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.55643/fcaptp.1.48.2023.3967
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Approach to Formation of Innovative Entrepreneurship`s Creative Potential

Abstract: In accordance with the basic statements of management science, which help to a based conceptual approach to the formation of innovative entrepreneurship`s creative potential, its elements are the purpose and objectives, objects and subjects, principles, functions and subsystems, consideration of which the most significant managerial influences and stages of the process of forming the creative potential of enterprises. The theoretical and methodological basis of scientific research were scientific concepts and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In work [9] it is noted that the development of dynamic capabilities of the personnel component of the enterprise creates conditions and opportunities for timely adjustment of the chosen strategy of its development, and increases the efficiency of their functioning. In the work [10], the authors substantiated the importance of the dynamic capabilities of personnel potential in relation to the implementation of its creative component in the innovative development of the enterprise. However, the authors, again, do not define the main parameters and characteristics of these possibilities.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…In work [9] it is noted that the development of dynamic capabilities of the personnel component of the enterprise creates conditions and opportunities for timely adjustment of the chosen strategy of its development, and increases the efficiency of their functioning. In the work [10], the authors substantiated the importance of the dynamic capabilities of personnel potential in relation to the implementation of its creative component in the innovative development of the enterprise. However, the authors, again, do not define the main parameters and characteristics of these possibilities.…”
Section: Literature Reviewmentioning
confidence: 97%
“…The analysis of publications [1][2][3][4][5][6][7][8][9][10] showed that most of the research in the field of effective management of the personnel potential of the enterprise is concentrated on the key features of personnel resources, paying less attention to the interaction of their dynamic capabilities and the formation of the competitiveness of business structures. Thus, significant efforts should be directed to the study of how the personnel of the enterprise, its dynamic capabilities and the nature of the business processes implemented by it affect the expected results of the enterprise.…”
Section: Literature Reviewmentioning
confidence: 99%